Educação bilíngue e interculturalidade : aspectos linguísticos e culturais na constituição de sujeitos bilíngues - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
This study analyzes the context of a bilingual program developed in a school in order to investigate the linguistic and cultural aspects that permeate the bilingual classroom. This is a case study (LÜDKE; ANDRÉ, 1986) of ethnographic nature (ANDRÉ, 2012) conducted in a 6th grade class of a private school located in Anápolis, Goiás. This study sought to first understand the context in which the program takes place, looking to the methodological and curricular choices to distinguish the type of bilingualism being developed, as well as the implications of language usage that imbues this space, especially the role of Portuguese (L1) in the process of linguistic and cultural development of the added language (AL), in this case English. The cultural traits of L1 and LA in the interactions in the classroom were also analyzed in order to perceive instances of interculturality in the process of bilingual education. Based on Grosjean (2013, 1982), García (2011), Baker (2006) and Mejía (2002) the concepts of bilingualism and bilingual education are presented to understand the underlining of the program studied. The concepts of linguistic mode (GROSJEAN, 2013) and translanguaging (CANAGARAJAH, 2013) are introduced to shed light on how bilinguals move between the languages that are available to them to establish communication. The concept of interculturality (CANDAU, 2011; WALSH, 2012; FLEURI, 2001) and the characteristics that describe the skills of an intercultural learner (BYRAM, 1997; CORBETT 2011) were explored. Bilingual education based on the intercultural approach (GARCÍA, 2011) and the sociocultural implications in the language learner’s life was also discussed. The study had twelve participants: eleven students and one teacher. The data was collected through the observation of classes that were recorded in video and audio, interviews and notes in a field journal. The results indicate that bilingual education developed through interculturality can promote a significant expansion in the making of linguistic-cultural meanings as learners become better acquainted with their language and culture and unfold the language and culture of others. Thus, languages and cultures must be worked through an integrated system (CANAGARAJAH, 2013) so that bilinguals can make the most of a space where two languages and cultures pervade and interact.
Keywords: Educação Bilíngue; Bilinguismo; Interculturalidade; Cultura; Bilingual Education; Bilingualism; Interculturality; Culture; CIENCIAS HUMANAS::EDUCACAO